1981
DOI: 10.1113/jphysiol.1981.sp013850
|View full text |Cite
|
Sign up to set email alerts
|

Mouse pancreatic acinar cells: voltage‐clamp study of acetylcholine‐evoked membrane current.

Abstract: 1. A two-micro-electrode voltage-clamp technique was applied to a study of the resting properties of mouse pancreatic acinar cell membranes and the action of acetylcholine (ACh). 2. The resting voltage-current relation was linear. The specific membrane resistance was calculated to be about 10 k omega cm2. This value was doubled after removal of Cl from the tissue bath superfusion solution. 3. At a holding potential equal to the spontaneous resting potential (about -35 mV) micro-ionophoretic ACh application evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Figure 2 shows voltage-clamp records of ACh-evoked transmembrane current and the measurement of EA(-.h under the control condition and during prolonged exposure to a Cl--free sulphate solution. The data from the voltage-clamp current recording experiments (McCandless et al 1981) are in good agreement with the earlier determination of EAch using potential recordings (Iwatsuki & Petersen, 1977b).…”
supporting
confidence: 85%
See 3 more Smart Citations
“…Figure 2 shows voltage-clamp records of ACh-evoked transmembrane current and the measurement of EA(-.h under the control condition and during prolonged exposure to a Cl--free sulphate solution. The data from the voltage-clamp current recording experiments (McCandless et al 1981) are in good agreement with the earlier determination of EAch using potential recordings (Iwatsuki & Petersen, 1977b).…”
supporting
confidence: 85%
“…That there is a regulated Na+ conductance pathway in the mouse pancreatic acinar cell membrane (Matthews & Petersen, 1973;Nishiyama & Petersen, 1975;McCandless et al 1981;Petersen et al 1981) is beyond doubt, but I misinterpreted the data in the salivary and lacrimal glands and erroneously concluded that there was also such a Na' conductance in these glands (Petersen, 1980a). This led to my strongly expressed belief that the stimulant-evoked Na+ influx through regulated channels in the basolateral membrane was the most important and general feature in all the exocrine STIMUL LUS-SECRETION COUPLINVG glands (Petersen, 1980a).…”
Section: Fluid Secretion Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of Rs on the observed transmembrahe currents was always negligible. The specific membrane resistance RM = Rr~A was calculated from R,~ and Cm assuming a specific membrane ca- Petersen & Philpott, 1981). tn many cases small clusters consisting of 2 to 5 cells were used instead of single cells for measuring alanine-driven currents.…”
Section: Electrical Cell Parametersmentioning
confidence: 99%